Surface-topography induced optical and magneto-optical anisotropy of permalloy gratings. (3rd July 2015) - Arregi, J A; González-Díaz, J B; Soriano, N; Mora, B; Berger, A
Abstract: We study the orientation dependence of the optical and magneto-optical properties of shallow permalloy gratings by using generalized magneto-optical ellipsometry. Our experimental findings show that the magnetic gratings behave as an artificial material system with an effective optical and magneto-optical anisotropy of uniaxial character, whose strength scales linearly with the height modulation of the surface topography. Thus, our results demonstrate that both optical and magneto-optical properties can be tuned by controlling the profile depth of a periodic structure. Additionally, we analyzed the magneto-optical signal of the gratings in diffraction geometry by means of full ellipsometric characterization. We find that the longitudinal and transverse magneto-optical Kerr effects in diffraction preserve the symmetry of the conventional reflection matrix, at least for light polarizations states that are not too far from the symmetry points of the reflection matrix. This particular finding should allow for a substantially expanded experimental characterization of magneto-optical effects in diffraction geometry.